Good, better, best? A comprehensive comparison of healthcare providers' performance: An application to physiotherapy practices in primary care. Issue 12 (December 2017) - Steenhuis, Sander; Groeneweg, Niels; Koolman, Xander; Portrait, France
Highlights: It is feasible to compare physiotherapists' performance using PROMs and PREMs. Significant and meaningful differences in performance were detected after case-mix correction. Incomplete data invalidated useful comparison, despite strong financial incentives for the physiotherapists. Abstract: Most payment methods in healthcare stimulate volume-driven care, rather than value-driven care. Value-based payment methods such as Pay-For-Performance have the potential to reduce costs and improve quality of care. Ideally, outcome indicators are used in the assessment of providers' performance. The aim of this paper is to describe the feasibility of assessing and comparing the performances of providers using a comprehensive set of quality and cost data. We had access to unique and extensive datasets containing individual data on PROMs, PREMs and costs of physiotherapy practices in Dutch primary care. We merged these datasets at the patient-level and compared the performances of these practices using case-mix corrected linear regression models. Several significant differences in performance were detected between practices. These results can be used by both physiotherapists, to improve treatment given, and insurers to support their purchasing decisions. The study demonstrates that it is feasible to compare the performance of providers using PROMs and PREMs. However, it would take an extra effort to increase usefulness and it remains unclear under which conditions this effort is cost-effective. Healthcare providers need to be aware of the added value of registering outcomes to improve their quality. Insurers need to facilitate this by designing value-based contracts with the right incentives. Only then can payment methods contribute to value-based healthcare and increase value for patients.